Hemp (Cannabis sativa L., Kompolti cv.) and Hop (Humulus lupulus L., Chinook cv.) Essential Oil and Hydrolate: HS-GC-MS Chemical Investigation and Apoptotic Activity Evaluation - Elisa Ovidi; Valentina Laghezza Masci; Anna Rita Taddei; Jacopo Torresi; William Tomassi; Matteo Iannone; Antonio Tiezzi; Filippo Maggi; Stefania Garzoli (MDPI AG, 2022)
In this study, essential oils (EOs) and hydrolates (Hys) from Italian hemp (Cannabis sativa L. Kompolti cv.) and hop (Humulus Lupulus L., Chinook cv.) supply chains were chemically characterized and tested to investigate their apoptotic potential for the first time. Headspace-Gas Chromatography-Mass Spectrometry (HS-GC-MS) techniques were performed to describe their volatile chemical profile, highlighting a composition rich in terpene derivatives such as monoterpenes and sesquiterpenes among which β-myrcene, limonene, β-caryophyllene and α-humulene were the main constituents of EOs; in contrast, linalool, cis-p-menth-2,8-dien-1-ol, terpinen-4-ol, α-terpineol, caryophyllene oxide, and τ-cadinol were found in the Hys. The cytotoxicity activity on human leukemia cells (HL60), human neuroblastoma cells (SH-SY5Y), human metastatic adenocarcinoma breast cells (MCF7), human adenocarcinoma breast cells (MDA), and normal breast epithelial cell (MCF10A) for the EOs and Hys was studied by MTT assay and cytofluorimetric analysis and scanning and transmission electron microscopy were performed to define ultrastructural changes and the mechanism of cells death for HL 60 cells. An induction of the apoptotic mechanism was evidenced for hemp and hop EOs after treatment with the corresponding EC50 dose. In addition, TEM and SEM investigations revealed typical characteristics induced by the apoptotic pathway. Therefore, thanks to the integration of the applied methodologies with the used techniques, this work provides an overview on the metabolomic profile and the apoptotic potential of hemp and hop EOs and, for the first time, also of Hys. The findings of this preliminary study confirm that the EOs and Hys from Cannabis and Humulus species are sources of bioactive molecules with multiple biological effects yet to be explored.